2017
DOI: 10.1002/1873-3468.12765
|View full text |Cite
|
Sign up to set email alerts
|

mRNPs meet stress granules

Abstract: Edited by Wilhelm JustStress granules are cytoplasmic structures that form in response to a variety of cellular stresses. They contain mRNAs and many proteins including numerous types of RNA-binding proteins, and have been studied in connection to major cellular events such as protein synthesis as well as disease. Despite the well-known fact that stress granules encapsulate mRNPs (mRNA-protein complexes), much of the research has naturally focused on the protein components of stress granules. The specific deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…It remains to be determined whether Gle1 selfassociation is a common determinant of its ability to stimulate other Dbps/DDXs. However, our analysis of the phosphodeficient gle1A 6A and phosphomimetic gle1A 6D suggests that phosphorylation may dictate the oligomerization state of Gle1A and During initiation of the stress response, Gle1A in its basally modified, self-associated state activates DDX3 functions and promotes SG formation (1). As eIF2␣ is phosphorylated and the integrated stress response proceeds, the activation of MAPK cascades stimulate ERK1/2 and JNK to phosphorylate a cluster of N-terminal Gle1A residues, which then primes GSK3 to phosphorylate additional residues in the Gle1A cluster (2).…”
Section: Phosphorylation Of Gle1a Regulates Ddx3 and Stress Responsementioning
confidence: 89%
See 1 more Smart Citation
“…It remains to be determined whether Gle1 selfassociation is a common determinant of its ability to stimulate other Dbps/DDXs. However, our analysis of the phosphodeficient gle1A 6A and phosphomimetic gle1A 6D suggests that phosphorylation may dictate the oligomerization state of Gle1A and During initiation of the stress response, Gle1A in its basally modified, self-associated state activates DDX3 functions and promotes SG formation (1). As eIF2␣ is phosphorylated and the integrated stress response proceeds, the activation of MAPK cascades stimulate ERK1/2 and JNK to phosphorylate a cluster of N-terminal Gle1A residues, which then primes GSK3 to phosphorylate additional residues in the Gle1A cluster (2).…”
Section: Phosphorylation Of Gle1a Regulates Ddx3 and Stress Responsementioning
confidence: 89%
“…To achieve this, nuclear export of nonessential transcripts is blocked, whereas temporally induced mRNA transcripts in protein complexes (mRNPs) 3 are selectively exported through nuclear pore complexes (NPCs) and then translated. Concurrently, general translation is inhibited, and a pre-existing pool of cytoplasmic mRNPs reversibly assembles into cytoplasmic stress granule (SG) complexes of RNA processing machinery, translation factors, and signaling proteins (1). In addition to the changes in gene expression profiles, the dynamics of mRNP occupancy in SGs affect rates of mRNA decay, global translational activity, and cell signaling cascades (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…This mechanism should impair nuclear import of L1 RNPs, thus affecting the retrotransposition process. SGs are cytoplasmic bodies induced in response to a variety of cellular stresses and accumulate untranslated mRNAs (Sheinberger and Shav-Tal 2017). It was previously reported that L1 RNA, ORF1p and ORF2p localize in SGs, together with several L1 RNP-associated proteins (Doucet et al 2010;Goodier et al 2007Goodier et al , 2012Goodier et al , 2015Gallois-Montbrun et al 2007;Moldovan and Moran 2015).…”
Section: Regulation Of Line-1 Expressionmentioning
confidence: 99%
“…RNA-binding proteins (RBPs) are interesting within this context, as they bind ribonucleic acid molecules, regulating their fate after transcription (Shi and Barna, 2015). RBPs contain low-complexity (LC) domains that mediate their condensation in ribonucleoprotein (RNP) granules, which exert a role in mRNA translation, metabolism, and transport (Sheinberger and Shav-Tal, 2017). These structures also mediate the response to cellular stress by assembling RBPs and their target mRNAs in stress granules (SGs), in which protein translation is repressed (Sheinberger and Shav-Tal, 2017).…”
Section: Introductionmentioning
confidence: 99%